Experimental investigation on the process of hydrate deposition using a rock-flow cell. (1st December 2021) - Liu, Xiang; Zhang, Jialu; Li, Yuxing; Ning, Yuanxing; Liu, Zhiming; Song, Guangchun; Wang, Wuchang
Highlights: The voltage signal was used to monitor the hydrate deposition process. The main factors affecting the deposits of bulk and gas hydrates were systematically studied. The secondary formation from the direct conversion of water to hydrate was observed in bulk phase. The growth rate of hydrate deposits under different conditions was quantitatively characterized. Abstract: Gas hydrates can readily form in deep-water oil and gas production processes and can lead to disruptions in flow conditions. In this work, in order to investigate the growth characteristics of hydrate in a gas–water system, a voltage detection system and a transparent rock-flow cell were used where a series of hydrate formation and flow experiments were conducted under different liquid holdups, rocking rates, and subcooling. For the gas–water system, the integrity of liquid film and gas–liquid contact area were important factors affecting gas phase and bulk hydrate formation respectively. In addition, the sudden transformation from water layer into hydrate deposits which captured by voltage and pressure signals was also an important factor affecting the volume of hydrate formation. Based on the voltage signal, the growth rate of gas hydrate and the effects of different factors were analyzed for the first time, gas-phase hydrate deposition can be divided into two stages: wall formation and film growth. The growth rate of the former is about 10 times faster than that of the latter. With the increase of the liquid holdup, the growth rate and duration of hydrate film decrease continuously, but only the duration of hydrate film decreases as the rotating speed decreasing. This work provides further insight on how the hydrate deposition in the gas–water system evolves in real-time.